2017
DOI: 10.1016/j.neuroscience.2016.11.036
|View full text |Cite
|
Sign up to set email alerts
|

Neuron-specific SUMO knockdown suppresses global gene expression response and worsens functional outcome after transient forebrain ischemia in mice

Abstract: Small ubiquitin-like modifier (SUMO) conjugation (SUMOylation) plays key roles in neurologic function in health and disease. Neuronal SUMOylation is essential for emotionality and cognition, and this pathway is dramatically activated in post-ischemic neurons, a neuroprotective response to ischemia. It is also known from cell culture studies that SUMOylation modulates gene expression. However, it remains unknown how SUMOylation regulates neuronal gene expression in vivo, in the physiologic state and after ische… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 41 publications
1
30
0
Order By: Relevance
“…A large body of evidence suggests that SUMOylation is an endogenous prosurvival pathway, and that increasing global SUMOylation protects the brain against ischemic insult 31, 32, 33. For example, transgenic mice that exhibit elevated basal levels of global SUMOylation are more resistant to ischemia‐induced brain damage,32 whereas transgenic mice in which SUMO expression is significantly silenced show worse functional outcome after global cerebral ischemia 31.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large body of evidence suggests that SUMOylation is an endogenous prosurvival pathway, and that increasing global SUMOylation protects the brain against ischemic insult 31, 32, 33. For example, transgenic mice that exhibit elevated basal levels of global SUMOylation are more resistant to ischemia‐induced brain damage,32 whereas transgenic mice in which SUMO expression is significantly silenced show worse functional outcome after global cerebral ischemia 31.…”
Section: Discussionmentioning
confidence: 99%
“…For example, transgenic mice that exhibit elevated basal levels of global SUMOylation are more resistant to ischemia‐induced brain damage,32 whereas transgenic mice in which SUMO expression is significantly silenced show worse functional outcome after global cerebral ischemia 31. Currently, only a limited number of small molecules that may be capable of increasing SUMOylation in vivo are available for testing in disease models related to I/R injury 33.…”
Section: Discussionmentioning
confidence: 99%
“…13,20 SUMOylation in experimental brain ischemia/stroke A substantial body of evidence has shown that both global and focal transient cerebral ischemia dramatically increase the levels of SUMO-conjugated proteins (especially SUMO2/3 conjugation) in rodent brains shortly after reperfusion, and that this process may be neuroprotective (summarized in Table 1). [3][4][5][21][22][23] However, it is prudent to note that evidence of SUMO activation in post-ischemic human brain tissue has yet to be put forward and should therefore be actively pursued.…”
Section: Sumoylation Pathwaymentioning
confidence: 99%
“…Based on a substantial body of evidence, it is now believed that SUMOylation is an endogenous neuroprotective mechanism (12,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). For example, in vitro studies have shown that silencing SUMOs sensitizes primary neurons to oxygen-glucose deprivation (OGD)induced damage, whereas overexpression of SUMO in cortical neurons induced OGD tolerance (12).…”
mentioning
confidence: 99%
“…For example, in vitro studies have shown that silencing SUMOs sensitizes primary neurons to oxygen-glucose deprivation (OGD)induced damage, whereas overexpression of SUMO in cortical neurons induced OGD tolerance (12). Furthermore, compared to wild-type mice, mice overexpressing Ubc9 demonstrated improved resistance to focal ischemia-induced damage (23), and transgenic mice in which SUMO-1-3 were knocked down in neurons displayed worse functional outcomes after transient forebrain ischemia (24). SUMOylation is increased during animal hibernation and clinically relevant hypothermia (12,18,25,26), and it has been proposed that increased global SUMOylation is a key mechanism underlying hypothermia-induced protection (12,18,21,27).…”
mentioning
confidence: 99%